Novel addition-fragmentation agent in cationic photopolymerization - Gupta, Mukesh Kumar; Mehare, Rupali S.; Singh, Raj Pal (Polymer Bulletin, 2010)
The aim of present study is to examine the photo-initiation efficiency of N,N-dimethylacrylamide-based allylic ammonium salt as one component addition-fragmentation agent (cationic photoinitiator cum radical source) in free radical accelerated cationic polymerization. Novel addition-fragmentation agent (AFA), 2-(N,N-dimethylcarboxy-3-propenyl)(phenylcarbonyl-4-phenylene) dimethyl ammonium hexafluoroantimonate (DMPDA) was synthesized as cationic photoinitiator and its initiation efficiency was examined in polymerization of cyclohexene oxide (CHO), isobutyl vinyl ether (IBVE), and n-butyl vinyl ether (n-BVE) in CH(2)Cl(2) solvent at wavelength lambda > 290 nm. The rate of polymerization increases with the increase in initiator concentration and reaction time. The results demonstrate that DMPDA acts as an efficient photoinitiator (AFA) without use of radical source in free radical accelerated cationic polymerization.
Keywords: Addition-fragmentation agent; Ammonium salt; Benzophenone; Cationic polymerization; Onium salt; Photopolymerization

Synthesis and characterization of a new diol-functionalized s-triazine-based polymerizable hindered amine light stabilizer - Mehare, Rupali S.; Lonkar, Sunil P.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2012)
A new diol-functionalized triazine-based polymerizable hindered amine light stabilizer (HALS) was synthesized in two steps. First, selective synthesis of an s-triazine containing two HALS moieties as substituents was accomplished by using phase-transfer catalysis. This step required the establishment of optimum reaction conditions (type of two-phase system, best solvent, and catalyst). In the second step, the substituted triazine was treated with diethanolamine to introduce polymerizable diol functionality. The resulting product should act as a light stabilizer, since it contains two HALS moieties anchored to a thermally stable s-triazine unit. Moreover, incorporation of the diol into a polymeric material might be expected to impart prolonged stability in weathering environments. Characterization of the diol was accomplished by using Fourier transform infrared spectroscopy (FTIR), `H NMR, and mass spectrometry. J. VINYL ADDIT. TECHNOL., 18:204208, 2012. (c) 2012 Society of Plastics Engineers

In situ synthesis of nitrogen- and sulfur-enriched hierarchical porous carbon for high-performance supercapacitor - Mehare, Rupali S.; Ranganath, Suresha P.; Chaturvedi, Vikash; Badiger, Manohar. V.; Shelke, Manjusha V. (Energy & Fuels, 2018)
In this work, we present a simple and facile method for the nitrogen (N)- and sulfur (S)- doped porous three-dimensional (3D) spongelike carbon materials via direct pyrolysis of N and S containing polymer N,N'-methylene-bis-acrylamide cross-linked poly(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonic acid) at varying temperatures under inert atmosphere. The obtained nitrogen- and sulfur-doped porous carbons (NSPCs) possess 3D hierarchical porous structure and contain a significantly high amount of N and S species. The concurrent incorporation of N and S successfully modified the surface properties of carbon materials and lead to enhanced capacitive performance. The presented NSPC exhibits specific capacitance of 230 F g(-1) at a current density of 1 A g(-1) and showed excellent cycling stability, depicting a promising material for energy storage devices.

Agro-waste extracted cellulose supported silver phosphate nanostructures as a green photocatalyst for improved photodegradation of RhB dye and industrial fertilizer effluents - Dwivedi, Pravin K.; Nair, Aathira; Mehare, Rupali S.; Chaturvedi, Vikash; Joshi, Kavita; Shelke, V. Manjusha (Nanoscale Advances, 2020)
The efficiency and reusability of photocatalysts are the dominant factors for their pragmatic use. The visible light induced semiconductor silver phosphate is a superior photocatalyst effective under visible light but its stability is still an undiscussed issue. To overcome this stability issue in this present manuscript, eco-friendly agro-waste extracted cellulose supported silver phosphate nanostructures have been designed for the first time through a simple chemical process. At first, silver phosphate nanostructures were synthesized by the co-precipitation method. Then, different weights of cellulose were added to the silver nitrate solution to form cellulose supported silver phosphate nanostructures. The photodegradation efficiency for each weight ratio was examined in which the photocatalyst Ag-8 nanostructures showed a high rate (0.024 min(-1)) for degradation of Rhodamine B (RhB) using a low intensity tungsten bulb. Real sample analysis has also been carried out using this photocatalyst for the degradation of industrial fertilizer effluents. The degradation rate of all the nanostructures was found to be high in comparison to pristine silver phosphate as well as the extracted bare cellulose. The photocatalytic activity is enhanced because of the participation of cellulose as a support which makes an interface for silver phosphate and assists it in delaying the charge recombination period under visible light. To understand the photochemical reaction of electrons and holes, scavenger studies were also performed.

Experimental and theoretical investigations of the effect of heteroatom-doped carbon microsphere supports on the stability and storage capacity of nano-Co3O4 conversion anodes for application in lithium-ion batteries - Dwivedi, Pravin K.; Nair, Aathira; Mehare, Rupali S.; Chaturvedi, Vikash; Joshi, Kavita; Shelke, V, Manjusha (Nanoscale Advances, 2020)
Conversion-type anode materials have been intensely studied for application in Li-ion batteries (LIBs) due to their potentially higher capacities than current graphite-based anodes. This work reports the development of a high-capacity and stable anode from a nanocomposite of N and S co-doped carbon spheres (NSCSs) with Co3O4 (NSCS-Co3O4). A hydrothermal reaction of saccharose withl-cysteine was carried out, followed by its carbonization. CSs when used as supports for conversion-type materials provide efficient electron/ion transfer channels, enhancing the overall electrochemical performance of the electrodes. Additionally, the heteroatoms doped in a carbon matrix alter the electronic properties, often increasing the reactivity of the carbon surface, and they are reported to be effective for anchoring metal oxide nanoparticles. Consequently, the NSCS-Co3O4 nanocomposites developed in this work exhibit enhanced and stable reversible specific capacity over several cycles. Stable cycling behavior was observed at 1 A g(-1)with 1285 mA h g(-1) of specific capacity retained after 350 cycles along with more than 99% of coulombic efficiency. This material shows excellent rate capability with a specific capacity of 745 mA h g(-1) retained even at a high current density of 5 A g(-1). Detailed DFT-based calculations revealed the role of doped supports in controlling the volume expansion upon lithiation.